Chemistry of endemic Tanacetum mucroniferum Hub.-Mor. & Grierson extracts and three new sesquiterpene lactones - Servi, Huseyin; Goren, Nezhun (Tubitak Scientific & Technological Research Council Turkey, 2019)
Tanacetum mucroniferum Hub.-Mor. & Grierson was collected from Sakaltutan in Erzincan Province of Turkey. Comparative phytochemical investigation was carried out on the ethyl acetate and methanol extracts of the plant. The secondary metabolites were isolated and purified by chromatographic methods such as column chromatography, medium pressure liquid chromatography, high-performance thin-layer chromatography, and preparative thin-layer chromatography. The extracts of the aerial parts of Tanacetum mucroniferum yielded three new sesquiterpene lactones and some known compounds, namely two sesquiterpene lactones, six flavonoids, three coumarins, and one triterpene. Structures of isolated compounds were determined by IR, UV, H-1 NMR, APT, COSY, HSQC, HMBC, NOESY, and MS (EI, CI) spin decoupling, and some chemical reactions were carried out.
Keywords: Tanacetum mucroniferum; sesquiterpene lactones; flavonoids; coumarin; triterpene; CONSTITUENTS; Chemistry; Engineering